PENGARUH APLIKASI DOSIS BIOCHAR SEKAM PADI DAN KONSENTRASI PUPUK ORGANIK CAIR (POC) LIMBAH CAIR TAHU TERHADAP KANDUNGAN HARA P-JARINGAN DAN HASIL TANAMAN KEDELAI (Glycne max L.) DI ALFISOL - Sangku, Efrem Kasimirus; Nguru, Elias St.O; Kapa, Max J (JURNAL AGRISA, 2025)
This research was carried out in Liliba, Oebobo sub-district, Kupang city, NTT, which took place from April to September 2023. The aim of this research was to determine the interaction effect of using rice husk biochar doses with the POC concentration of tofu liquid waste on the P nutrient content and yield. soybean plants, to determine the effect of rice husk biochar dosage on the P nutrient content and soybean crop yields and to determine the effect of POC concentration of tofu liquid waste on the P nutrient content and soybean crop yields in Alfisol. This research is a factorial experiment designed using a completely randomized design (RAL). The first factor is the rice husk biochar dose (B), which consists of 4 levels, namely: no biochar dose (B0), rice husk biochar dose 10 tons/ha (B1), rice husk biochar dose 15 tons/ha (B2), and rice husk biochar dosage of 20 tons/ha (B3). The second factor is the POC concentration of tofu liquid waste (T) which consists of 4 levels, namely: no POC concentration of tofu liquid waste (TO), POC concentration of tofu liquid waste 15% (T1), POC concentration of tofu liquid waste 30% (T2) , and the POC concentration of tofu liquid waste is 45% (T3). Thus, there were 16 treatment combinations and they were made in 3 replications so that in total there were 48 experimental units. The results showed that different doses of rice husk biochar gave no significant effect on the nutrient content of P-tissue which was 0.195% and gave the best dry weight of soybean seeds at a dose of 15 tons/ha (B2) which amounted to 9.27 grams/plant. The difference in the concentration of POC tofu liquid waste affects the best tissue P nutrient content at a concentration of 150 ml/l (T1) which is 0.199%, the best soybean seed dry weight is at a concentration of 450 ml/l (T3) which is 8.1 grams/plant and the best soybean plant oven dry seed weight is at a concentration of 150 ml/l (T1) which is 3.8 grams/plant.